Faith Alone: The Doctrine of Justification - Calvin Wu (Jurnal Amanat Agung, 2018)
Schreiner, Thomas R. Faith Alone: The Doctrine of Justification (Grand Rapids: Zondervan, 2015), xxi + 323 halaman. Edisi kindle.